Association of vancomycin trough levels, AUC and AUC/MIC ratios with clinical outcomes in patients with enterococcal bacteremia: a prospective cohort study - Eda Kubra Sel; Berfu Tufan; Gundag Kupra Atagun; Vildan Avkan Oguz; Ozgen Alpay Ozbek; Mukaddes Gumustekin; Serife Reyhan Ucku; Ayse Gelal (BMC Infectious Diseases)
Abstract Background The optimal vancomycin pharmacokinetic/pharmacodynamic (PK/PD) targets for successful treatment of enterococcal infections remain controversial. To clarify these targets, this study investigated the association of the vancomycin area under the curve (AUC), the AUC/minimum inhibitory concentration (MIC) ratio, and the serum trough concentration (Ctrough) with clinical outcomes (treatment efficacy, safety, and 30-day mortality) in adult patients with enterococcal bacteremia. Methods This prospective cohort study was conducted at a tertiary university hospital between January 2023–2025 and included adult patients with enterococcal bacteremia who were treated with vancomycin and met predefined inclusion/exclusion criteria. Data were prospectively collected. The associations of the steady-state 24-hour vancomycin AUC (AUCss), the AUCss/MIC ratio, and the trough concentration (Ctrough−ss) with treatment efficacy, safety, and 30-day mortality were evaluated. Bayesian modeling was used to estimate the AUC. Optimal vancomycin PK/PD cutoff values were determined using receiver operating characteristic (ROC) curve analysis. Results Among the 53 patients included in the study, treatment was effective in 62.3%, while acute kidney injury (AKI) developed in 47.2%. The 30-day all-cause mortality rate was 28.3%. Regarding treatment efficacy, only the AUCss cutoff value was found to be statistically significant; patients with AUCss<616 µg·h/mL had a higher rate of efficacy compared to those with AUCss≥616 µg·h/mL (p = 0.031). A similar pattern was observed for mortality at this cutoff value (p = 0.041). The highest efficacy was observed in the 400–616 µg·h/mL range (18 out of 22 patients, 82%). The cutoff values for AKI were determined to be 538 µg·h/mL for AUCss and 15.7 µg/mL for Ctrough−ss. Acute kidney injury occurred in 68.8% of patients with AUCss≥538 µg·h/mL and in 14.3% of those with AUCss<538 µg·h/mL (p < 0.001). Similarly, the risk of AKI was significantly greater in patients with Ctrough−ss≥15.7 µg/mL than in those with Ctrough−ss<15.7 µg/mL (p < 0.001). Conclusions In patients with enterococcal bacteremia treated with vancomycin, adjusting the dose to achieve an AUCss between 400 and 616 µg·h/mL may be appropriate to ensure effective therapy. However, due to the risk of AKI at these doses, patients should be closely monitored. For safe treatment in cases where AUC monitoring is not feasible, maintaining a serum Ctrough−ss below 15.7 µg/mL may be appropriate.